2013 5th International Conference on Computer Science and Information Technology 2013
DOI: 10.1109/csit.2013.6588782
|View full text |Cite
|
Sign up to set email alerts
|

Software cost estimation based on use case points for global software development

Abstract: this paper investigates the applicability of Use Case Point estimation model to global software project development. Nowadays, there is growing trend among leading software companies to outsource their project geographically, in countries with lower labor rate. This new trend increases competitiveness in the software market, which in turn shortens the development lifecycle time. This leads to several challenges in project management, especially global project management. Effort and cost estimation are two of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 15 publications
0
19
0
2
Order By: Relevance
“…The final scores can be seen in Table II-E. Three studies were excluded due to their low quality score. The lists with the included and excluded studies after the study selection and quality assessment are shown in Table II-E. TABLE III INCLUDED AND EXCLUDED WORKS AFTER THE STUDY SELECTION AND QUALITY ASSESSMENT Included works Excluded works S7 [9], S10 [32], S1 [33], S2 [34], S3 [35], S4 [36], S5 [37], S11 [38], S6 [39], S8 [10], S9 [40], S12 [41], S13 [42], S15 [7], S20 [8] S14 [43], S16 [44], S17 [45], S18 [46], S19 [47], S21 [48], S22 [49], S23 [50], S24 [51], D1 [52] F. Data extraction…”
Section: E Study Quality Assessmentmentioning
confidence: 99%
“…The final scores can be seen in Table II-E. Three studies were excluded due to their low quality score. The lists with the included and excluded studies after the study selection and quality assessment are shown in Table II-E. TABLE III INCLUDED AND EXCLUDED WORKS AFTER THE STUDY SELECTION AND QUALITY ASSESSMENT Included works Excluded works S7 [9], S10 [32], S1 [33], S2 [34], S3 [35], S4 [36], S5 [37], S11 [38], S6 [39], S8 [10], S9 [40], S12 [41], S13 [42], S15 [7], S20 [8] S14 [43], S16 [44], S17 [45], S18 [46], S19 [47], S21 [48], S22 [49], S23 [50], S24 [51], D1 [52] F. Data extraction…”
Section: E Study Quality Assessmentmentioning
confidence: 99%
“…Los factores ambientales y t茅cnicos son propensos al sesgo influenciado por la experiencia del estimador (Alves, Valente & Nunes, 2013) y no presentan estandarizaci贸n (Ayy谋ld谋z, Ko莽yi臒it & Peker, 2013). Azzeh propone la inclusi贸n de 3 nuevos factores ambientales con el fin de ayudar a obtener mayor precisi贸n en los resultados (Azzeh, 2013). Asimismo, Jha, Jena y Malu introducen 6 nuevos factores ambientales a fin de ayudar a obtener mayor precisi贸n en los resultados (Jha, Jena & Malu, 2014).…”
Section: Discusionesunclassified
“…Otros trabajos futuros restantes como una estandarizaci贸n de casos de uso (Rem贸n & Thomas, 2010), calibraci贸n de los pesos de casos de uso (Nassif, Ho & Capretz, 2013), consideraci贸n de diversos factores de complejidad (Azzeh, 2013) y actualizaci贸n de los factores ambientales y t茅cnicos (Nassif, Ho & Capretz, 2013); ya han sido evidenciados como materia de estudio por diversos autores en la presente investigaci贸n. …”
Section: Discusi贸n 2: Acerca De Los Futuros Trabajos a Realizar Para unclassified
“…This study suggests that the UCP can be used as an alternative to estimate software development projects on a global scale by modifying the environmental factors of the original UCP [9].…”
Section: Literature Reviewmentioning
confidence: 99%